2012
DOI: 10.1080/17522439.2012.733405
|View full text |Cite
|
Sign up to set email alerts
|

Sex and schizophrenia: a review of gender differences

Abstract: Gender differences in schizophrenia have been noted since conceptualisation of the illness. Female onset is typically later, with a second peak post-menopause. Whilst incidence is higher in men, prevalence does not differ. Research has explored possible biopsychosocial causes of these differences. Evidence for genetic and neurodevelopmental factors is weak but support has garnered for the "estrogen hypothesis," which emphasises the possible neuroprotective effect of estrogen in women. Differences have also bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 53 publications
1
54
1
2
Order By: Relevance
“…Research has demonstrated gender-specific differences in terms of symptoms, course and outcome for a range of psychiatric disorders. [2][3][4][5][6] Environmental factors may also impact differently on male and female behaviour, 7 and the time-points at which environmental factors exert their influence differ between men and women. 8 As pointed out by Walder et al, 9 improved delineation of gender differences during the prodrome of psychosis may offer important value in terms of (i) elucidating theoretical models, including a dimensional perspective of psychosisproneness; (ii) understanding the neurobiological underpinnings of psychosis; and (iii) constructing algorithms for risk prediction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has demonstrated gender-specific differences in terms of symptoms, course and outcome for a range of psychiatric disorders. [2][3][4][5][6] Environmental factors may also impact differently on male and female behaviour, 7 and the time-points at which environmental factors exert their influence differ between men and women. 8 As pointed out by Walder et al, 9 improved delineation of gender differences during the prodrome of psychosis may offer important value in terms of (i) elucidating theoretical models, including a dimensional perspective of psychosisproneness; (ii) understanding the neurobiological underpinnings of psychosis; and (iii) constructing algorithms for risk prediction.…”
Section: Introductionmentioning
confidence: 99%
“…1 The main gender differences reported in schizophrenia are more pronounced negative symptoms and a higher propensity to comorbid substance abuse, poorer social functioning and earlier age at onset in men, and more affective symptoms in women. 6,[10][11][12][13] To our knowledge, only three published studies have explicitly addressed the issue of gender differences in HR subjects using state-of-the-art instruments. 9,14,15 Willhite et al investigated gender differences in positive, negative and disorganized symptoms, and in social support and functioning, in 68 HR subjects (male, n = 49; female, n = 19; average age on inclusion 17 years).…”
Section: Introductionmentioning
confidence: 99%
“…While 26% of patients were males in subgroup 1, all patients were males in the remaining two subgroups. It is worth noting that gender differences in schizophrenia is well-established 33,34,35 , so imbalance in the male/female proportion across the subgroups are not entirely surprising. Compared with the remaining two subgroups, the first derived subgroup showed a trend towards high proportion of positive family history of mental illness and paranoid schizophrenia.…”
Section: Application To Scz Patientsmentioning
confidence: 99%
“…The link between trauma, particularly early childhood and sexual abuse, and the later development of AVH appears to be a solid one [14,56,57]. Failure of inhibition may generate intrusive thoughts, which are increased in schizophrenia, despite also occurring in other mental illnesses and even in healthy individuals.…”
Section: The Neurocognitive Modelsmentioning
confidence: 99%